2019
DOI: 10.1055/s-0039-1688694
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Foramen Magnum in Dry Human Skulls in Northeastern Brazil

Abstract: Introduction The successful identification of the deceased is vital to the progress of any forensic investigation. This process of identification is facilitated by the determination of age, gender, and ethnicity. One of the main biological traits to be established from skeletal remains is the gender of the individual. In situations in which there are fragmented and mutilated skeletal remains, gender determination is relatively difficult, and it becomes important to establish the accuracy of individual bones. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For the first time, the collection at the NeuroZone3D Research Center in Peru provides detailed measurements of the foramen magnum and condyles in cadaveric specimens [Table 5]. In comparison, studies from Colombia and Brazil [15,19,33] revealed similar measurements for the foramen magnum; however, they did not detail condyle measurements, limiting the comprehensive comparison between these anatomical samples. e NeuroZone3D Research Center collection stands out for its specific focus on both measurements, contributing to a more comprehensive understanding of craniovertebral morphology compared to studies from Colombia and Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the first time, the collection at the NeuroZone3D Research Center in Peru provides detailed measurements of the foramen magnum and condyles in cadaveric specimens [Table 5]. In comparison, studies from Colombia and Brazil [15,19,33] revealed similar measurements for the foramen magnum; however, they did not detail condyle measurements, limiting the comprehensive comparison between these anatomical samples. e NeuroZone3D Research Center collection stands out for its specific focus on both measurements, contributing to a more comprehensive understanding of craniovertebral morphology compared to studies from Colombia and Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were conducted using conventional measurement techniques with a soft, inelastic measuring tape (Perfect Measuring Tape Company, USA). A single researcher assessed each skull, determining six cranial measurements according to widely recognized nomenclature[ 4 , 12 , 15 , 21 , 41 ] with assistance from other authors.…”
Section: Mateials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation